School Law for the Principal, A Handbook for Practitioners - Joan L. Curcio; Amy C. Milford (Educational Considerations, 1992)
A book review of School Law for the Principal, A Handbook for Practitioners, by Robert J. Shoop and Dennis R. Dunklee.